Comparison of two digital intraoral radiography imaging systems as a function of contrast resolution and exposure time - Cesur Aydın, Kader; Demirel, O?uzhan; Özcan, Mutlu (Edizioni Minerva Medica, 2020)
Background: To compare the image quality of two different digital imaging systems; one photostimulable phosphor plate system (PSP) and a direct digital radiography system with CMOS imaging sensor; via evaluating contrast resolution among four different exposure times. Methods: Endodontically treated incisor teeth embedded in paraffin blocks are aligned next to a 99.5% Al wedge and exposed for 0.8, 0.1,0.125 and 0.16 seconds using both the CMOS and PSP systems. Using ImageJ software, 5 isometric and isogridded ROI from each root filling area and isometric ROI from the Al stepwedge were calculated. Results: Evaluation of the total of 120 images displayed that PSP system produced significantly higher contrast resolution (P<0.05) in regard to pixel values than the CMOS. The CMOS system was non- responsive to increasing dose (P=0.000). Regarding the EqAl values, no significant difference was determined between groups (P>0.05). Conclusions: The contrast resolution was higher using the PSP system. It can be estimated that, filling material will be more obvious under lower doses using PSP.
Keywords: Radiography; Dental; Technology; Radiologic; Diagnostic Equipment